2023
DOI: 10.1002/anie.202302883
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the Fucose Migration Product during Mass‐Spectrometric analysis of Blood Group Epitopes

Abstract: Fucose is a signaling carbohydrate that is attached at the end of glycan processing. It is involved in a range of processes, such as the selectin‐dependent leukocyte adhesion or pathogen‐receptor interactions. Mass‐spectrometric techniques, which are commonly used to determine the structure of glycans, frequently show fucose‐containing chimeric fragments that obfuscate the analysis. The rearrangement leading to these fragments—often referred to as fucose migration—has been known for more than 25 years, but the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…20–24 However, it has been observed that – in a process similar to peptide scrambling 25 – electrospray ionization (ESI) or collision-induced dissociation (CID) can alter the glycan sequence which results in additional non-native fragments being recorded in the mass spectrum. 26–33 Although the phenomenon is associated mostly with fucose-containing protonated glycans – hence it is often called fucose migration 28,34–37 – similar rearrangements have been observed for rhamnose, 38 mannose, 39 and xylose. 40 The structural motifs that trigger this rearrangement, as well as its mechanism and likelihood of occurrence, remain unknown after more than 40 years since their first observation.…”
Section: Introductionmentioning
confidence: 75%
“…20–24 However, it has been observed that – in a process similar to peptide scrambling 25 – electrospray ionization (ESI) or collision-induced dissociation (CID) can alter the glycan sequence which results in additional non-native fragments being recorded in the mass spectrum. 26–33 Although the phenomenon is associated mostly with fucose-containing protonated glycans – hence it is often called fucose migration 28,34–37 – similar rearrangements have been observed for rhamnose, 38 mannose, 39 and xylose. 40 The structural motifs that trigger this rearrangement, as well as its mechanism and likelihood of occurrence, remain unknown after more than 40 years since their first observation.…”
Section: Introductionmentioning
confidence: 75%
“…The calculations were performed in Gaussian16 using hybrid exchange-correlation PBE1PBE augmented with D3 dispersion correction and a 6-311+G­(d,p) basis set. This level of theory yields accurate conformational energies of mono- and disaccharides, and has been used to determine structures of carbohydrates and glycosyl intermediates . To simulate the effect of the solvent, we selected SMD continuous solvation model due to its extended parametrization, including nonelectrostatic effects, for biochemically relevant molecules .…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have made noteworthy discoveries regarding glycan rearrangements during collisions at specific energies. These observations include rearrangements of hexose, 10 rhamnose, 11 mannose, 10 xylose, 12 and fucose, initially reported by Ernst et alin 1997 13 and more recently shown in studies by Acs et al 14 and Lettow et al, 15 among others. 16,17 The results of these studies emphasized the critical importance of setting precise thresholds for particular fragments.…”
mentioning
confidence: 82%